Environment-friendly high-flame-retardant cable and preparation method thereof
Through the synergistic flame retardant system of modified brûlite powder and nitrogen-phosphorus silicon flame retardant, combined with silane polyolefin compatibilizer and EVA, the problem of insufficient flame retardant and mechanical properties of cable materials is solved, and cable materials with high flame retardant and excellent mechanical properties are achieved.
Patent Information
- Application Number
- CN202510021937.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-01-07
AI Technical Summary
Existing cable materials produce a large amount of toxic gases and smoke during combustion, and their flame retardant and mechanical properties are insufficient, making it difficult to meet environmental protection and safety requirements.
By using modified brûlite powder and nitrogen-phosphorus silicon flame retardant, combined with silane polyolefin compatibilizer and ethylene-vinyl acetate copolymer (EVA), a synergistic flame retardant system is formed to enhance the flame retardant and mechanical properties of the cable material.
It realizes the high flame retardant performance and excellent mechanical properties of cable materials, while increasing the flexibility of the material, meeting environmental protection and safety requirements.
Smart Images

Figure BDA0005231639120000051 
Figure BDA0005231639120000061 
Figure BDA0005231639120000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cable materials, and in particular to an environmentally friendly and highly flame-retardant cable and a preparation method thereof. Background Art
[0002] As an important carrier for power transmission and information transmission, the safety and environmental performance of wires and cables are increasingly attracting people's attention. With the enhancement of people's environmental awareness, halogen-free flame-retardant materials have gradually become the first choice for wires and cables in various industries. Polyethylene (PE) has become the most commonly used matrix for low-smoke halogen-free flame-retardant cable materials due to its halogen-free molecules, low dielectric loss, high insulation performance and price advantage. According to statistics, the number of fires caused by electrical reasons in the country accounts for about 30% of the total number of fires, of which fires caused by aging wires account for more than half of the total electrical fires. Traditional cable materials will produce a large amount of toxic gases and smoke when burning, which seriously threatens people's life, health and property safety. Therefore, it is of great significance to develop an environmentally friendly and highly flame-retardant cable material.
[0003] At present, the flame retardant cables commonly seen on the market mainly improve their flame retardant properties by adding flame retardants and using flame retardant materials. Commonly used inorganic flame retardants such as magnesium hydroxide and aluminum hydroxide contain more hydroxyl groups on their surfaces and have greater polarity, while PE is a non-polar molecule, which leads to the thermodynamic incompatibility between the two and greatly reduces the mechanical properties of low-smoke halogen-free flame retardant PE composite materials. Due to the incompatibility between PE and flame retardants, inorganic particles are easily agglomerated, and PE has a high degree of crystallinity, which will lead to higher hardness of cable materials produced by PE-based composite materials, which brings certain difficulties to the actual installation and laying. Patent No. CN118772518A discloses a cable composite material with halogen-free flame retardant functionality and a preparation method thereof. Diatomaceous earth with a surface modified with a nitrogen-phosphorus synergistic reactive flame retardant is prepared as an inorganic modifier and added to a high-density polyethylene substrate. The rich pores exposed by the diatomaceous earth and the synergistic flame retardant of the nitrogen-phosphorus synergistic flame retardant are utilized to enhance the flame retardant properties of the polyethylene cable material. However, the inorganic modifier has poor compatibility with the cable matrix and still has the problem of easy agglomeration. In addition, the flame retardant properties of the diatomaceous earth itself are limited, and the problem of poor flexibility of polyethylene is not improved, which is not conducive to market promotion and application.
[0004] Brucite has the advantages of abundant reserves, environmental friendliness, low toxicity and smoke suppression, and has attracted much attention. However, the addition amount of brucite often needs to be more than 60% to meet the flame retardant requirements. Such a high filling amount will lead to a significant decrease in the mechanical properties and processing properties of the material, and cannot meet the needs of practical applications. Based on this, the present invention utilizes the excellent flame retardant properties of brucite powder itself, and modifies it through the prepared nitrogen-phosphorus-silicon flame retardant. The siloxane in its structure is similarly compatible with the silane polyolefin compatibilizer, and the advantages of the synergistic flame retardancy of brucite powder and nitrogen-phosphorus-silicon are brought into play. The material has good mechanical properties and flame retardant properties, and at the same time increases the flexibility of the cable material, thereby meeting the increasingly stringent application requirements of the wire and cable industry. Summary of the invention
[0005] The purpose of the present invention is to solve the problems existing in the above-mentioned prior art and to provide an environmentally friendly and highly flame-retardant cable and a preparation method thereof, so as to improve the flame retardant properties of the cable material so that it has excellent mechanical properties and is green, environmentally friendly and pollution-free.
[0006] The present invention is achieved through the following technical solutions:
[0007] A method for preparing an environmentally friendly and highly flame-retardant cable is carried out according to the following steps:
[0008] Step (1), adding ultrafine brucite powder and ethanol to a reaction flask, stirring at a speed of 800-1000 r / min, adding a nitrogen-phosphorus-silicon flame retardant modifier, reacting at 60-70° C. for 20-40 minutes, filtering, washing with deionized water, drying and grinding to obtain nitrogen-phosphorus-silicon modified brucite powder.
[0009] Step (2), 70-80 parts by weight of LLDPE, 8-15 parts of EVA, 5-10 parts of silane polyolefin compatibilizer, 2-8 parts of nitrogen-phosphorus-silicon modified brucite powder, 0.5-0.8 parts of antioxidant, 2-3 parts of lubricant and 0.2-0.5 parts of ultraviolet absorber are placed in a mixer, stirred at a speed of 1200-1500r / min for 40-60min to form a uniform mixture, and then the mixture is fed into an extruder through a feeding hopper, the extrusion temperature is controlled to be 260-280°C, the screw speed is 300-350r / min, extrusion granulation, placed in warm water for cross-linking, pelletized, and molded to obtain a flame retardant protective cover material, and then extruded and compounded in the order of conductive core, insulating layer, and flame retardant protective cover material from the inside to the outside to obtain an environmentally friendly and highly flame retardant cable.
[0010] Furthermore, in step (1), the ratio of the ultrafine brucite powder to the nitrogen-phosphorus-silicon flame retardant modifier is 100 g:(90-120) g.
[0011] Furthermore, in step (2), the antioxidant is antioxidant 1010, the lubricant is polyethylene wax, and the ultraviolet absorber is UV-329.
[0012] Furthermore, in step (2), the compression molding temperature is 150-170° C., the pressure is 8-12 MPa, and the time is 10-15 min.
[0013] Furthermore, the preparation method of the nitrogen-phosphorus-silicon flame retardant modifier in step (1) is carried out according to the following steps:
[0014] Step S1. Under a nitrogen atmosphere, add triallyl isocyanurate and methanol to a reaction flask, stir evenly, add bis(4-methoxyphenyl)phosphine oxide, react at 45-60° C. for 5-8 h, concentrate under reduced pressure, add dichloromethane and mix evenly, add boron tribromide dropwise under an ice bath, react at 0° C. for 12-24 h, extract with ethyl acetate and deionized water, and purify by column chromatography (dichloromethane / methanol=20:1 elution) to obtain a polyhydroxyphosphorus nitrogen intermediate.
[0015] Step S2, under a nitrogen atmosphere, add a polyhydroxyphosphorus nitrogen intermediate and N,N-dimethylformamide to a reaction flask, stir evenly, add triethylamine and 3-isocyanatepropyltrimethoxysilane, stir to react, after the reaction is completed, concentrate under reduced pressure, wash with n-pentane, and dry to obtain a nitrogen-phosphorus-silicon flame retardant modifier.
[0016] Furthermore, in step S1, the ratio of triallyl isocyanurate, bis(4-methoxyphenyl)phosphine oxide, and boron tribromide is 1 mol:(3.1-3.5) mol:(6.5-8) mol.
[0017] Furthermore, in step S2, the ratio of the polyhydroxyphosphorus nitrogen intermediate, triethylamine, and 3-isocyanatepropyltrimethoxysilane is 1 mol: (5.5-6.2) mol: (7-8.5) mol.
[0018] Furthermore, in step S2, the reaction temperature is 100-120° C., and the reaction time is 8-16 h.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] (1) Brucite powder itself has certain flame retardant properties. The MgO generated by its thermal decomposition has high activity and heat resistance. It can form a dense protective film on the surface of polyethylene and convert toxic combustible gases such as CO into harmless CO2, thereby reducing the generation of toxic smoke. It has excellent smoke suppression effect, so that the material will not cause secondary pollution to the environment even after combustion, which is safe and environmentally friendly. Nitrogen-phosphorus-silicon flame retardant can decompose to produce non-combustible gases such as N2 and CO2, which can dilute combustible gases and reduce the oxygen concentration in the combustion area, thereby slowing down the combustion rate. At the same time, it can quickly form an expanded carbon layer at high temperature, isolate oxygen and heat, protect the polyethylene matrix, and prevent continuous combustion, thereby greatly enhancing the flame retardant properties of cable materials. Nitrogen-phosphorus-silicon elements synergize with brucite powder, which can play a role in the condensed phase to promote the carbonization of polymers, and can also remove high-energy free radicals in the combustion area. The combination of the two can achieve better flame retardant effects under lower usage conditions.
[0021] (2) The surface-modified brucite powder has a smaller particle size and can be added to polyethylene as a filler to fill the gaps between polyethylene molecular chains, increase the density of the material, and thus improve the mechanical strength of the material. The uniform dispersion of brucite powder in polyethylene can form many tiny stress concentration points, which can disperse stress when subjected to external forces, preventing the material from breaking due to excessive local stress.
[0022] (3) EVA has good flexibility, similar structure to LLDPE, and good compatibility. After blending, it can make up for the lack of toughness of polyethylene; part of the silicon-oxygen bonds on the surface of the nitrogen-phosphorus-silicon flame retardant modifier can produce chemical bonds with the hydroxyl groups on the surface of the brucite powder, so that the nitrogen-phosphorus-silicon flame retardant modifier is stably present on the surface of the brucite and is not easy to migrate and precipitate; the other part of the silicon-oxygen bonds can be hydrolyzed by the silane polyolefin compatibilizer under warm water conditions, so that a Si-O-Si cross-linked structure is formed between the polyethylene matrix, which improves the interface compatibility and makes the brucite powder evenly "embedded" in the polyethylene system to form a physical cross-linked core, which plays a role in stress absorption and load transfer. DETAILED DESCRIPTION
[0023] The present invention is further illustrated below through the description of specific implementation modes, but this is not a limitation of the present invention. Those skilled in the art can make various modifications or improvements based on the basic idea of the present invention, but as long as they do not deviate from the basic idea of the present invention, they are all within the scope of the present invention.
[0024] Unless otherwise specified, the raw materials and reagents used in this application are commercially available or can be prepared by known methods.
[0025] EVA: Ethylene-vinyl acetate copolymer, Taiwan Plastics Corporation.
[0026] LLDPE: Linear low-density polyethylene, Sinopec.
[0027] Triallyl isocyanurate, CAS number is 1025-15-6.
[0028] Bis(4-methoxyphenyl) oxide, CAS number is 15754-51-5.
[0029] 3-Isocyanatepropyltrimethoxysilane, CAS number is 15396-00-6.
[0030] Preparation of silane polyolefin compatibilizer: EVA:LLDPE raw materials in a mass ratio of 3:7, 3% of dibenzoyl peroxide and 2% of vinyltrimethoxysilane are mixed evenly, and then poured into a torque rheometer, and melt grafting is carried out at 120°C, the rotation speed is 30r / min, and the reaction time is 15min to obtain material A; after the roller temperature of the double roller is preheated to 120°C, 100g of EVA and 2g of dibutyltin dilaurate are added, the mixture is mixed evenly, taken out, cooled to room temperature, and crushed to obtain material B; material A and material B are mixed evenly on the double roller in a mass ratio of 95:5, and after complete plasticization, the roller is lowered and sheeted to obtain a silane polyolefin compatibilizer.
[0031] Example 1
[0032] (1) Under nitrogen atmosphere, add 65 mmol of triallyl isocyanurate and 260 mL of methanol to a reaction flask, stir evenly, add 208 mmol of bis(4-methoxyphenyl)phosphine oxide, react at 55°C for 6 h, concentrate under reduced pressure, add dichloromethane and mix evenly, add 481 mmol of boron tribromide dropwise under ice bath, react at 0°C for 16 h, extract with ethyl acetate and deionized water, purify by column chromatography (dichloromethane / methanol = 20:1 elution), and obtain a polyhydroxyphosphorus nitrogen intermediate. The preparation reaction formula is as follows:
[0033]
[0034] (2) Under nitrogen atmosphere, add 60 mmol of polyhydroxyphosphorus nitrogen intermediate and 510 mL of N,N-dimethylformamide to the reaction flask, stir evenly, add 357 mmol of triethylamine and 480 mmol of 3-isocyanate propyltrimethoxysilane, react at 110° C. for 12 h, concentrate under reduced pressure, wash with n-pentane, and dry to obtain nitrogen-phosphorus-silicon flame retardant modifier. The preparation reaction formula is as follows:
[0035]
[0036] (3) 10 g of ultrafine brucite powder and 260 mL of ethanol were added to a reaction flask, and after being stirred evenly at a speed of 900 r / min, 9 g of nitrogen-phosphorus-silicon flame retardant modifier was added, and the mixture was reacted at 65° C. for 30 min, filtered, washed with deionized water, dried and ground to obtain nitrogen-phosphorus-silicon modified brucite powder.
[0037] (4) 78 g of LLDPE, 8 g of EVA, 8 g of silane polyolefin compatibilizer, 2 g of nitrogen-phosphorus-silicon modified brucite powder, 0.65 g of antioxidant 1010, 2.5 g of polyethylene wax and 0.3 g of UV-329 were placed in a mixer and stirred at a speed of 1400 r / min for 50 min to form a uniform mixture. The mixture was then fed into an extruder through a feeding hopper, the extrusion temperature was controlled to be 270°C, the screw speed was controlled to be 320 r / min, extrusion granulation was performed, and the mixture was placed in 90°C warm water for cross-linking for 8 h. After pelletizing and compression molding, the compression molding temperature was 160°C, the pressure was 10 MPa, and the time was 12 min to obtain a flame retardant protective sheath material, and then extruded and compounded in the order of copper conductor, polyethylene insulation material, and flame retardant protective sheath material from the inside to the outside to obtain an environmentally friendly and highly flame retardant cable.
[0038] Example 2
[0039] (1) Under a nitrogen atmosphere, 150 mmol of triallyl isocyanurate and 450 mL of methanol were added to a reaction flask, and after stirring, 465 mmol of bis(4-methoxyphenyl)phosphine oxide was added, and the mixture was reacted at 60° C. for 5 h. The mixture was concentrated under reduced pressure, and dichloromethane was added and mixed evenly. 975 mmol of boron tribromide was added dropwise in an ice bath, and the mixture was reacted at 0° C. for 12 h. The mixture was extracted with ethyl acetate and deionized water, and purified by column chromatography (elution with dichloromethane / methanol=20:1) to obtain a polyhydroxyphosphorus nitrogen intermediate.
[0040] (2) Under nitrogen atmosphere, 130 mmol of polyhydroxyphosphorus nitrogen intermediate and 910 mL of N,N-dimethylformamide were added to a reaction flask, and after stirring, 715 mmol of triethylamine and 910 mmol of 3-isocyanatepropyltrimethoxysilane were added, and the mixture was reacted at 120 °C for 8 h. The mixture was concentrated under reduced pressure, washed with n-pentane, and dried to obtain a nitrogen-phosphorus-silicon flame retardant modifier.
[0041] (3) Add 10 g of ultrafine brucite powder and 200 mL of ethanol to a reaction flask, stir evenly at a speed of 1000 r / min, add 10 g of nitrogen-phosphorus-silicon flame retardant modifier, react at 70° C. for 20 min, filter, wash with deionized water, dry and grind to obtain nitrogen-phosphorus-silicon modified brucite powder.
[0042] (4) 75 g of LLDPE, 10 g of EVA, 5 g of silane polyolefin compatibilizer, 3.5 g of nitrogen-phosphorus-silicon modified brucite powder, 0.8 g of antioxidant 1010, 2 g of polyethylene wax and 0.5 g of UV-329 were placed in a mixer and stirred at a speed of 1500 r / min for 40 min to form a uniform mixture. The mixture was then fed into an extruder through a feeding hopper, the extrusion temperature was controlled to be 280°C, the screw speed was controlled to be 350 r / min, extrusion granulation was performed, and the mixture was placed in 90°C warm water for cross-linking for 8 h. After pelletizing and compression molding, the compression molding temperature was 170°C, the pressure was 12 MPa, and the time was 10 min to obtain a flame retardant protective sheath material, and then extruded and compounded in the order of copper conductor, polyethylene insulation material, and flame retardant protective sheath material from the inside to the outside to obtain an environmentally friendly and highly flame retardant cable.
[0043] Example 3
[0044] (1) Under a nitrogen atmosphere, 40 mmol of triallyl isocyanurate and 200 mL of methanol were added to a reaction flask. After stirring, 140 mmol of bis(4-methoxyphenyl)phosphine oxide was added, and the mixture was reacted at 45° C. for 8 h. The mixture was concentrated under reduced pressure, and dichloromethane was added and mixed evenly. 320 mmol of boron tribromide was added dropwise under an ice bath, and the mixture was reacted at 0° C. for 24 h. The mixture was extracted with ethyl acetate and deionized water, and purified by column chromatography (elution with dichloromethane / methanol=20:1) to obtain a polyhydroxyphosphorus nitrogen intermediate.
[0045] (2) Under nitrogen atmosphere, 35 mmol of polyhydroxyphosphorus nitrogen intermediate and 245 mL of N,N-dimethylformamide were added to a reaction flask, and after stirring, 217 mmol of triethylamine and 297.5 mmol of 3-isocyanatepropyltrimethoxysilane were added, and the mixture was reacted at 100 °C for 16 h. The mixture was concentrated under reduced pressure, washed with n-pentane, and dried to obtain a nitrogen-phosphorus-silicon flame retardant modifier.
[0046] (3) Add 10 g of ultrafine brucite powder and 300 mL of ethanol to a reaction flask, stir evenly at a speed of 800 r / min, add 10.8 g of nitrogen-phosphorus-silicon flame retardant modifier, react at 60° C. for 40 min, filter, wash with deionized water, dry and grind to obtain nitrogen-phosphorus-silicon modified brucite powder.
[0047] (4) 80 g of LLDPE, 12 g of EVA, 10 g of silane polyolefin compatibilizer, 5 g of nitrogen-phosphorus-silicon modified brucite powder, 0.8 g of antioxidant 1010, 3 g of polyethylene wax and 0.2 g of UV-329 were placed in a mixer and stirred at a speed of 1200 r / min for 60 min to form a uniform mixture. The mixture was then fed into an extruder through a feeding hopper, the extrusion temperature was controlled to be 260°C, the screw speed was controlled to be 300 r / min, extrusion granulation was performed, and the mixture was placed in 90°C warm water for cross-linking for 8 h. After pelletizing and compression molding, the compression molding temperature was 150°C, the pressure was 8 MPa, and the time was 15 min to obtain a flame retardant protective sheath material, and then the copper conductor, polyethylene insulation material, and flame retardant protective sheath material were extruded and compounded in order from the inside to the outside to obtain an environmentally friendly and highly flame retardant cable.
[0048] Example 4
[0049] (1) Under a nitrogen atmosphere, 100 mmol of triallyl isocyanurate and 420 mL of methanol were added to a reaction flask. After stirring, 325 mmol of bis(4-methoxyphenyl)phosphine oxide was added, and the mixture was reacted at 55° C. for 7 h. The mixture was concentrated under reduced pressure, and dichloromethane was added and mixed evenly. 720 mmol of boron tribromide was added dropwise under an ice bath, and the mixture was reacted at 0° C. for 15 h. The mixture was extracted with ethyl acetate and deionized water, and purified by column chromatography (elution with dichloromethane / methanol=20:1) to obtain a polyhydroxyphosphorus nitrogen intermediate.
[0050] (2) Under nitrogen atmosphere, 80 mmol of polyhydroxyphosphorus nitrogen intermediate and 680 mL of N,N-dimethylformamide were added to a reaction flask, and after stirring, 472 mmol of triethylamine and 615 mmol of 3-isocyanatepropyltrimethoxysilane were added, and the mixture was reacted at 115 °C for 10 h. The mixture was concentrated under reduced pressure, washed with n-pentane, and dried to obtain a nitrogen-phosphorus silicon flame retardant modifier.
[0051] (3) 10 g of ultrafine brucite powder and 265 mL of ethanol were added to a reaction flask, and after being stirred evenly at a speed of 950 r / min, 11.5 g of nitrogen-phosphorus-silicon flame retardant modifier was added, and the mixture was reacted at 70° C. for 35 min, filtered, washed with deionized water, dried and ground to obtain nitrogen-phosphorus-silicon modified brucite powder.
[0052] (4) 72 g of LLDPE, 14 g of EVA, 7 g of silane polyolefin compatibilizer, 6.5 g of nitrogen-phosphorus-silicon modified brucite powder, 0.6 g of antioxidant 1010, 2.4 g of polyethylene wax and 0.4 g of UV-329 were placed in a mixer and stirred at a speed of 1450 r / min for 45 min to form a uniform mixture. The mixture was then fed into an extruder through a feeding hopper, the extrusion temperature was controlled to be 275°C, the screw speed was controlled to be 330 r / min, extrusion granulation was performed, and the mixture was placed in 90°C warm water for cross-linking for 8 h. After pelletizing and compression molding, the compression molding temperature was 165°C, the pressure was 9 MPa, and the time was 12 min to obtain a flame retardant protective sheath material, and then the copper conductor, polyethylene insulation material, and flame retardant protective sheath material were extruded and compounded in the order of from the inside to the outside to obtain an environmentally friendly and highly flame retardant cable.
[0053] Example 5
[0054] (1) Under a nitrogen atmosphere, 52 mmol of triallyl isocyanurate and 235 mL of methanol were added to a reaction flask. After stirring, 176.8 mmol of bis(4-methoxyphenyl)phosphine oxide was added, and the mixture was reacted at 55° C. for 6 h. The mixture was concentrated under reduced pressure, and dichloromethane was added and mixed evenly. 390 mmol of boron tribromide was added dropwise in an ice bath, and the mixture was reacted at 0° C. for 18 h. The mixture was extracted with ethyl acetate and deionized water, and purified by column chromatography (elution with dichloromethane / methanol=20:1) to obtain a polyhydroxyphosphorus nitrogen intermediate.
[0055] (2) Under nitrogen atmosphere, 45 mmol of polyhydroxyphosphorus nitrogen intermediate and 370 mL of N,N-dimethylformamide were added to a reaction flask, and after stirring, 260 mmol of triethylamine and 352 mmol of 3-isocyanatepropyltrimethoxysilane were added, and the mixture was reacted at 105 °C for 16 h. The mixture was concentrated under reduced pressure, washed with n-pentane, and dried to obtain a nitrogen-phosphorus-silicon flame retardant modifier.
[0056] (3) Add 10 g of ultrafine brucite powder and 300 mL of ethanol to a reaction flask, stir evenly at a speed of 850 r / min, add 12 g of nitrogen-phosphorus-silicon flame retardant modifier, react at 65° C. for 40 min, filter, wash with deionized water, dry and grind to obtain nitrogen-phosphorus-silicon modified brucite powder.
[0057] (4) 75 g of LLDPE, 15 g of EVA, 9 g of silane polyolefin compatibilizer, 8 g of nitrogen-phosphorus-silicon modified brucite powder, 0.65 g of antioxidant 1010, 3 g of polyethylene wax and 0.3 g of UV-329 were placed in a mixer and stirred at a speed of 1350 r / min for 55 min to form a uniform mixture. The mixture was then fed into an extruder through a feeding hopper, the extrusion temperature was controlled to be 275°C, the screw speed was controlled to be 330 r / min, extrusion granulation was performed, and the mixture was placed in 90°C warm water for cross-linking for 8 h. After pelletizing and molding, the molding temperature was 160°C, the pressure was 10 MPa, and the time was 15 min to obtain a flame retardant protective sheath material, and then the copper conductor, polyethylene insulation material, and flame retardant protective sheath material were extruded and compounded in order from the inside to the outside to obtain an environmentally friendly and highly flame retardant cable.
[0058] Comparative Example 1
[0059] 78g of LLDPE, 8g of EVA, 8g of silane polyolefin compatibilizer, 2g of nitrogen-phosphorus-silicon flame retardant modifier (prepared by Example 1), 0.65g of antioxidant 1010, 2.5g of polyethylene wax and 0.3g of UV-329 were placed in a mixer and stirred at a speed of 1400r / min for 50min to form a uniform mixture, and then the mixture was fed into an extruder through a feeding hopper, the extrusion temperature was controlled to be 270°C, the screw speed was 320r / min, extrusion granulation was carried out, and the mixture was placed in 90°C warm water for cross-linking for 8h, pelletized and molded at a molding temperature of 160°C, a pressure of 10MPa and a time of 12min to obtain a protective sheath material, and then extruded and compounded in the order of copper conductor, polyethylene insulation material and protective sheath material from the inside to the outside to obtain a cable material.
[0060] Comparative Example 2
[0061] 78g of LLDPE, 8g of EVA, 8g of silane polyolefin compatibilizer, 2g of ultrafine brucite powder, 0.65g of antioxidant 1010, 2.5g of polyethylene wax and 0.3g of UV-329 were placed in a mixer and stirred at a speed of 1400r / min for 50min to form a uniform mixture, and then the mixture was fed into an extruder through a feeding hopper, the extrusion temperature was controlled to be 270°C, the screw speed was 320r / min, extrusion granulation was carried out, and the mixture was placed in 90°C warm water for cross-linking for 8h, pelletized and molded at a molding temperature of 160°C, a pressure of 10MPa, and a time of 12min to obtain a protective sheath material, and then extruded and compounded in the order of copper conductor, polyethylene insulation material, and protective sheath material from the inside to the outside to obtain a cable material.
[0062] Comparative Example 3
[0063] 78g of LLDPE, 8g of EVA, 8g of silane polyolefin compatibilizer, 0.65g of antioxidant 1010, 2.5g of polyethylene wax and 0.3g of UV-329 were placed in a mixer and stirred at a speed of 1400r / min for 50min to form a uniform mixture. The mixture was then fed into an extruder through a feeding hopper, the extrusion temperature was controlled to be 270°C, the screw speed was 320r / min, extrusion granulation was carried out, and the mixture was placed in 90°C warm water for cross-linking for 8h. The mixture was pelletized and molded at a molding temperature of 160°C, a pressure of 10MPa, and a time of 12min to obtain a protective sheath material, which was then extruded and compounded in the order of copper conductor, polyethylene insulation material, and protective sheath material from the inside to the outside to obtain a cable material.
[0064] Tensile strength: According to GB / T1040 standard, a microcomputer-controlled electronic universal testing machine was used to stretch the specimen with a size of 150mm×150mm×2mm and a stretching speed of 200mm / min. The test was repeated 5 times and the average value was taken.
[0065] Notched impact strength: According to GB / T1043 standard, the specimen size is 100mm×10mm×4mm, the notch depth is 2mm, the notch shape is V-shaped, the pendulum speed is 2.9m / s, and the average value is taken after 5 tests.
[0066] Table 1 Mechanical properties test
[0067]
[0068] From the test results in the above table, it can be seen that with the increase of the content of nitrogen-phosphorus-silicon modified brucite powder, the mechanical properties of the cable material are significantly improved, among which the tensile strength in Example 4 reaches 45.8MPa and the impact strength is 21.2kJ / m 2This is because, on the one hand, the surface-modified brucite powder has a small particle size and can be added to polyethylene as a filler to fill the gaps between polyethylene molecular chains and increase the density of the material. The uniform dispersion of brucite powder in polyethylene can form many tiny stress concentration points, which can disperse stress when subjected to external forces and prevent the material from breaking due to excessive local stress, thereby improving the mechanical strength of the material. On the other hand, part of the silicon-oxygen bonds on the surface of the nitrogen-phosphorus-silicon flame retardant modifier can chemically bond with the hydroxyl groups on the surface of the brucite powder, making the nitrogen-phosphorus-silicon flame retardant modifier stably present on the surface of the brucite , not easy to migrate and precipitate; the other part of the silicon-oxygen bond can be hydrolyzed by the silane polyolefin compatibilizer under warm water conditions, so that a Si-O-Si cross-linked structure is formed between the polyethylene matrix, which improves the interface compatibility and makes the brucite powder evenly "embedded" in the polyethylene system to form a physical cross-linked core, which plays a role in stress absorption and load transfer; at the same time, EVA has good flexibility, similar to LLDPE in structure and good compatibility. After blending, it can make up for the shortcomings in performance and improve the interaction between interfaces. When the material is subjected to force, the stress at the interface is more evenly transferred, which increases the elongation at break of the material.
[0069] Limiting oxygen index test: Tested in accordance with GB / T2406.1-2008.
[0070] Vertical burning grade test: Tested in accordance with GB / T2408-1996.
[0071] Table 2 Flame retardant performance test
[0072]
[0073] Brucite powder itself has certain flame retardant properties. The MgO generated by its thermal decomposition has high activity and heat resistance. It can form a dense protective film on the surface of polyethylene, and at the same time convert toxic combustible gases such as CO into harmless CO2, thereby reducing the generation of toxic smoke. It has excellent smoke suppression effects, so that the material has no secondary pollution to the environment even after combustion, which is safe and environmentally friendly. Nitrogen-phosphorus-silicon flame retardants can decompose to produce non-combustible gases such as N2 and CO2, which can dilute combustible gases and reduce the oxygen concentration in the combustion area, thereby slowing down the combustion rate. At the same time, it can quickly form an expanded carbon layer at high temperatures, isolate oxygen and heat, protect the polyethylene matrix, and prevent continuous combustion, thereby greatly enhancing the flame retardant properties of cable materials. Nitrogen-phosphorus-silicon elements synergize with brucite powder, which can play a role in the condensed phase, promote the carbonization of polymers, and remove high-energy free radicals in the combustion area. The combination of the two can achieve better flame retardant effects under lower usage conditions.
[0074] Comparative Example 1 is a single nitrogen-phosphorus-silicon synergistic flame retardant. Since the load transfer effect of brucite powder cannot be utilized, the mechanical properties and flame retardant properties are reduced to varying degrees. At the same time, the small molecule flame retardant has problems such as migration and precipitation, resulting in poor overall flame retardant properties of the material; the brucite powder in Comparative Example 2 has not been surface-modified, has poor compatibility with the polyethylene matrix, and has interface problems, resulting in the inability to efficiently exert the advantages of the brucite powder, so the mechanical properties are slightly reduced; Comparative Example 3 does not contain nitrogen-phosphorus-silicon flame retardant and brucite powder, and has the worst mechanical properties and flame retardant properties.
[0075] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing an environmentally friendly and highly flame-retardant cable, characterized in that: The preparation method is carried out according to the following steps: Step (1), adding ultrafine brucite powder and ethanol to a reaction flask, stirring at a speed of 800-1000 r / min, adding a nitrogen-phosphorus-silicon flame retardant modifier, reacting at 60-70° C. for 20-40 min, filtering, washing with deionized water, drying and grinding to obtain nitrogen-phosphorus-silicon modified brucite powder; Step (2), placing 70-80 parts of LLDPE, 8-15 parts of EVA, 5-10 parts of silane polyolefin compatibilizer, 2-8 parts of nitrogen-phosphorus-silicon modified brucite powder, 0.5-0.8 parts of antioxidant, 2-3 parts of lubricant and 0.2-0.5 parts of ultraviolet absorber in a mixer, stirring at a speed of 1200-1500r / min for 40-60min to form a uniform mixture, then feeding the mixture into an extruder through a feeding hopper, controlling the extrusion temperature to 260-280°C, the screw speed to 300-350r / min, extruding granulation, placing in warm water for cross-linking, pelletizing, and molding to obtain a flame retardant protective cover material, and then extruding and compounding in the order of a conductive core, an insulating layer, and a flame retardant protective cover material from the inside to the outside to obtain an environmentally friendly and highly flame retardant cable.
2. The method for preparing an environmentally friendly and highly flame-retardant cable according to claim 1, characterized in that: In the step (1), the ratio of the ultrafine brucite powder to the nitrogen-phosphorus-silicon flame retardant modifier is 100 g:(90-120) g.
3. The method for preparing an environmentally friendly and highly flame-retardant cable according to claim 1, characterized in that: In the step (2), the antioxidant is antioxidant 1010, the lubricant is polyethylene wax, the ultraviolet absorber is UV-329, the conductive wire core is a copper conductor, and the insulating layer is a polyethylene insulating material.
4. The method for preparing an environmentally friendly and highly flame-retardant cable according to claim 1, characterized in that: In the step (2), the compression molding temperature is 150-170° C., the pressure is 8-12 MPa, and the time is 10-15 min.
5. The method for preparing an environmentally friendly and highly flame-retardant cable according to claim 1, characterized in that: The preparation method of the nitrogen-phosphorus-silicon flame retardant modifier in step (1) is carried out according to the following steps: Step S1, under a nitrogen atmosphere, add triallyl isocyanurate and methanol to a reaction flask, stir evenly, add bis(4-methoxyphenyl)phosphine oxide, react at 45-60° C. for 5-8 hours, concentrate under reduced pressure, add dichloromethane and mix evenly, add boron tribromide dropwise under an ice bath, react at 0° C. for 12-24 hours, extract with ethyl acetate and deionized water, and purify by column chromatography to obtain a polyhydroxyphosphorus nitrogen intermediate; Step S2, under a nitrogen atmosphere, add a polyhydroxyphosphorus nitrogen intermediate and N,N-dimethylformamide to a reaction flask, stir evenly, add triethylamine and 3-isocyanatepropyltrimethoxysilane, stir to react, after the reaction is completed, concentrate under reduced pressure, wash with n-pentane, and dry to obtain a nitrogen-phosphorus-silicon flame retardant modifier.
6. The method for preparing an environmentally friendly and highly flame-retardant cable according to claim 5, characterized in that: In the step S1, the ratio of triallyl isocyanurate, bis(4-methoxyphenyl)phosphine oxide and boron tribromide is 1 mol:(3.1-3.5) mol:(6.5-8) mol.
7. The method for preparing an environmentally friendly and highly flame-retardant cable according to claim 5, characterized in that: In the step S2, the ratio of the polyhydroxyphosphorus nitrogen intermediate, triethylamine, and 3-isocyanatepropyltrimethoxysilane is 1 mol: (5.5-6.2) mol: (7-8.5) mol.
8. The method for preparing an environmentally friendly and highly flame-retardant cable according to claim 5, characterized in that: In step S2, the reaction temperature is 100-120° C. and the reaction time is 8-16 hours.
9. An environmentally friendly and highly flame-retardant cable, characterized in that: Obtained by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Irradiation-crosslinked halogen-free flame-retardant photovoltaic cable, and preparation method and application thereof
CN106432895A
Fire-fighting flame-retardant cable material and preparation method thereof
CN115926298A
Environment-friendly flame-retardant adhesive
CN116200145A
Phosphorus-nitrogen-silicon multi-element flame retardant as well as preparation method and application thereof
CN117229322A
High-molecular light-weight automobile mask and production process thereof
CN118388945A